Anticipation or avoidance: internal medicine resident experiences performing invasive bedside procedures - Louis, Alyssa S; Lee, Christie; Page, Andrea V; Ginsburg, Shiphra (Canadian Medical Education Journal, 2023)
Background: Internal Medicine (IM) residents are required to perform bedside procedures for diagnostic and therapeutic purposes. Residents’ experiences with procedures vary widely, for unclear reasons. Objective: To explore IM residents’ experiences with performing bedside procedures and to identify barriers and facilitators to obtaining sufficient experience. Methods: Using an inductive, thematic approach, we conducted five individual semi-structured interviews and one focus group with seven IM residents (12 residents in total) during the 2017-2018 academic year at a Canadian tertiary care centre. We used iterative, open-ended questions to elicit residents’ experiences, and barriers and facilitators, to performing bedside procedures. Transcripts were analyzed for themes using Braun and Clarke’s method. Results: We identified four themes 1) Patient-specific factors such as body habitus and procedure urgency; 2) Systems factors such as time constraints and accessibility of materials; 3) Faculty factors including availability to supervise, comfort level, and referral preferences, and 4) Resident-specific factors including preparation, prior experiences, and confidence. Some residents expressed procedure-related anxiety and avoidance. Conclusion: Educational interventions aimed to improve procedural efficiency and ensure availability of supervisors may help facilitate residents to perform procedures, yet may not address procedure-related anxiety. Further study is required to understand better how procedure-averse residents can gain confidence to seek out procedures.